Association of Serum Uric Acid Status With Bone Mineral Density in Adolescents Aged 12–19 Years - Pan, Kaiyu; Yao, Xiaocong; Liu, Minbo; Zhu, Zhongxin (Frontiers in Medicine, 2020)
Aims: Evidence linking serum uric acid (sUA) and bone mineral density (BMD) in adolescents is very limited. To the best of our knowledge, only one report has focused on the relationship between sUA and BMD in adolescents. Thus, this study aimed to determine the association between sUA and total BMD in adolescents aged 12–19 years. Methods: A cross-sectional study was conducted on a sample composed of non-institutionalised US population from the National Health and Nutrition Examination Survey. Weighted multivariate linear regression models were used to evaluate the association between sUA and total BMD. Subgroup analyses were further performed. Results: sUA positively correlated with total BMD in the multiple regression model after adjusting for potential confounders. However, in the subgroup analyses stratified by sex, age, or race/ethnicity, the association between sUA and total BMD followed an inverted U-shaped curve in female adolescents, adolescents aged 16–19 years, and other race/ethnicity. Conclusions: Our results suggested that the correlation between sUA level and total BMD differed by sex. The increased sUA level would be beneficial to bone health in adolescents with low sUA levels, but for female adolescents, a higher sUA level (turning point, 3.9 mg/dL) may have an adverse effect on bone health.